Animal Agency in Iron-Age Sicilian Art (VIII-VI BCE): Interaccion between Bovines and Man - López-Bertran, Mireia; Ferrer, Meritxell (Boletín de Arte, 2019)
This paper proposes an analysis of the relationship between bovines and humans through the lens of animal agency, using various artworks recovered from the site of Polizzello (western Sicily) dated between the 8th and the 6th centuries BCE. Specifically, we study a group of table amphorae decorated with bucrania, together with representations of these animals and hybrid beings painted on clay dishware. First, we will explain briefly the historical context and the artistic traditions of the island. Next, we will describe the site of Polizzello and the range of artworks. Finally, we will discuss these objects under the lens of the so-called «animal-studies» to highlight the important role of the bovines in human social dynamics.